A history of women artists: [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present] - Munsterberg, Hugo (C. N. Potter : distributed by Crown Publishers, 1975)
A history of women artists : [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present]
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques